High-risk breast cancer surveillance with MRI: 10-year experience from the German consortium for hereditary breast and ovarian cancer - Bick, Ulrich; Engel, Christoph; Krug, Barbara; Heindel, Walter; Fallenberg, Eva M.; Rhiem, Kerstin; Maintz, David; Golatta, Michael; Speiser, Dorothee; Rjosk-Dendorfer, Dorothea; Laemmer-Skarke, Irina; Dietzel, Frederic; et al. (Breast Cancer Research and Treatment, 2019)
Purpose: To report on 10 years of high-risk service screening with annual MRI in the German Consortium for Hereditary Breast and Ovarian Cancer (GC-HBOC). Methods: A cohort of 4,573 high-risk, previously unaffected women (954 BRCA1 carriers, 598 BRCA2 carriers, 3021 BRCA1/2 non-carriers) participating in the GC-HBOC surveillance program was prospectively followed. Screening outcomes for 14,142 screening rounds with MRI between 2006 and 2015 were analyzed and stratified by risk group, type of screening round, and age. Results: A total of 221 primary breast cancers (185 invasive, 36 in situ) were diagnosed within 12 months of an annual screening round with MRI. Of all cancers, 84.5% (174/206, 15 unknown) were stage 0 or I. In BRCA1 carriers, 16.9% (10/59, 5 unknown) of all incident cancers (screen-detected and interval cancers combined) and in BRCA2 carriers 12.5% (3/24, 4 unknown) were stage IIA or higher, compared to only 4.8% (2/42, 2 unknown) in high-risk BRCA1/2 non-carriers. Program sensitivity was 89.6% (95% CI 84.9–93.0) with no significant differences in sensitivity between risk groups or by age. Specificity was significantly lower in the first screening round (84.6%, 95% CI 83.6–85.7) than in subsequent screening rounds (91.1%, 95% CI 90.6–91.7), p < 0.001. Cancer detection rates (CDRs) and as a result positive predictive values were strongly dependent on type of screening round, risk group and patient age. CDRs ranged from 43.5‰ (95% CI 29.8–62.9) for the first screening round in BRCA2 carriers to 2.9‰ (95% CI 1.3–6.3) for subsequent screening rounds in high-risk non-carriers in the age group 30 to 39 years. Conclusions: High-risk screening with MRI was successfully implemented in the GC-HBOC with high sensitivity and specificity. Risk prediction and inclusion criteria in high-risk non-carriers need to be adjusted to improve CDRs and thus screening efficacy in these patients.
CRIS-Team Scopus Importer:2022-11-17
Keywords: BRCA1 gene; BRCA2 gene; Breast cancer; Early detection of cancer; Hereditary breast and ovarian cancer syndrome; Magnetic resonance imaging